Pengaruh Konflik dan Alienasi Kaum Proletar terhadap Masyarakat Sudan dalam Novel “Al-Junqu Masamirul Ardh” - Miolo, Syahrul Alfitrah; Sutaman, Sutaman; Yurisa, Penny Respati (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2025)
The capitalist system implemented in an area will inevitably give rise to conflict and social alienation as well as bad influences that can be felt by society. The study of Marxism was born as a form of criticism of the capitalist system and a solution to the problems caused by capitalism, namely social conflict and alienation. The aims of this research is to reveal the impact of conflict and proletariat alienation on Sudanese society. This research uses qualitative research methods, with a Marxist literary sociology approach. There are two data sources, namely primary data sources and secondary data sources. Data collection was carried out through reading techniques and note-taking techniques. In analyzing the data, researchers used the Miles, Huberman, and Saldana analysis model in which there are three stages, namely data condensation, data presentation, and conclusion drawing. The results of this research is the effects arising from the conflict and alienation experienced by proletariat towards Sudanese society in the novel